Utilizing Information "Shape" as an Interface Metaphor Based on Genre - Toms, Elaine G.; Campbell, D. Grant (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Documents have conventions which have evolved within discourse communities and which facilitate document use. These conventions are represented in a document by visual cues that define a shape and serve as an interface metaphor in a user's interaction with a digital document. In this paper we report on the results of two studies, one of which examined the impact of . . .